Managed Aquifer Recharge for Water Resilience - Dillon, Peter; Fernández Escalante, Enrique; Megdal, Sharon B.; Massmann, Gudrun (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a hard copy of the editorial and all the papers in a Special Issue of the peer-reviewed open access journal 'Water' on the theme 'Managed Aquifer Recharge for Water Resilience'. Managed aquifer recharge (MAR) is the purposeful recharge of water to aquifers for subsequent recovery or environmental benefit. MAR is increasingly used to make water supplies resilient to drought, climate change and deteriorating water quality, and to protect ecosystems from declining groundwater levels. Global MAR has grown exponentially to 10 cu.km/year and will increase ten-fold within a few decades. Well informed hydrogeologists, engineers and water quality scientists are needed to ensure that this investment is effective in meeting increasingly pressing needs. This compilation contains lessons from many examples of existing projects, including several national and continental summaries. It also addresses the elements essential for identifying and advancing projects such as mapping aquifer suitability and opportunities, policy matters, operational issues, and some innovations in MAR methods and monitoring. This collection exemplifies the state of progress in the science and practice of MAR and is intended to be useful, at least to water managers, water utilities, agricultural water users and urban planners, to facilitate water resilience through new MAR projects.